Ribosomal protein L9 is a potential therapeutic target for B-ALL through the activation of the p53 signaling pathway - Li, Xinxin; Meng, Wenting; Wang, Xi; Huang, Siyong; Wang, Jianbin; Liang, Han; Si, Dailing (Frontiers in Immunology, 2025)
B-cell acute lymphocytic leukemia (B-ALL) is a malignant hematological disorder marked by the aberrant proliferation of abnormal B lymphocytes. Although recent advancements have highlighted the pivotal role of ribosomes in the progression of B-ALL, the specific function of ribosomal protein L9 (RPL9), a key component of ribosomal structural protein, still unclear. In this study, we observed a significant upregulation of RPL9 in human B-ALL cells compared to normal B cells, suggesting RPL9’s potential key role in B-ALL progression. Enforced RPL9 knockdown (KD) led to decreased proliferation and increased apoptosis in B-ALL cells compared to the control group. Furthermore, RPL9 KD significantly extended the survival time of NCG mice bearing B-ALL cells in vivo compared to controls. Mechanistically, our findings indicate that RPL9 KD triggers nucleolar stress, disrupts ribosome biosynthesis, and activates the p53 signaling pathway. Building upon our recent investigation into the positive regulatory influence of FTO on m6A-modified RPL9, we discovered that FTO overexpression can mitigate the activation of p53 signaling induced by RPL9 KD. Our findings further suggest that RPL9 KD increases MICA/B mRNA and protein expression in B-ALL cells, which serves as crucial ligands of NK cell’s NKG2D, potentially heightening their sensitivity to NK cell-mediated cytotoxicity. In summary, our study suggests that RPL9 KD suppresses B-ALL proliferation and upregulates immunotherapy targets, highlighting the important role of RPL9 as a potential target for conventional and immunotherapy of B-ALL.